Analisis Distribusi Beban Velg Sepeda Motor Listrik Dengan Variasi Motif Spoke Menggunakan Metode Elemen Hingga - Illahi, Putra Kurnia; Karohika, I Made Gatot; Parwata, I Made (Teknik Desain Mekanika, 2024)
Abstract Motorcycles are something that everyone needs. The types of motorbikes are also increasingly varied, one of which is an electric motorbike. An important component of an electric motorcycle is the wheels. Wheels have an important role as attachment to the tire and also distribute the power generated by the engine. Wheels are designed to have high strength to withstand a given load. With the development of computer technology, it allows us to do simulations or tests of the strength and safety values of wheels to avoid wheel failure. This study aims to determine the strength and safety value of the wheels with variations in the spoke model through the simulations carried out. The simulation was carried out using the Autodesk Inventor 2021 software. The load given was in the form of a pressure of 0.05 MPa and a moment of 4000 N.mm. From the simulations carried out, it was found that type A wheels have a von misses stress of 3.034 MPa, a displacement of 0.002255 mm, and a safety factor of 15. Wheels with type B have a von misses stress of 2.613 MPa, a displacement of 0.002229 mm, and a safety factor of 15. While vekg with type C has a von misses stress of 1.807 MPa, a displacement of 0.002099 mm, and a safety factor of 15. Keywords: Wheels, Simulation, Safety factor